Enhancing surface properties with coconut oil/cocoa butter/chia seed/titanium dioxide: Innovations in water-based coating technologies - Ozturk, Nazlican; Sahin, Fatma Irem; Acarali, Nil (WILEY, 2025)
The aim of the present study was to enhance water-based coating technologies by using additives. The physical and chemical properties of a water-based organic coating were improved by incorporating coconut oil, cocoa butter, chia seed, and titanium dioxide into the coating. Cocoa butter was added to enhance the hydrophobic properties of the coating. To increase its corrosion-resistant properties, coconut oil was also included. Chia seed was added to observe its adhesion effect on the water-based coating. Titanium dioxide, obtained as waste from a pharmaceutical company, was supplied and added to the coating to both maintain color change and improve the durability of the coating. The additives were added to the water-based coating in different proportions ranging from 0% to 6% by weight. For the experiments in this study, Design Expert Box-Behnken method was applied by selecting three levels and four parameters. The optimal experiment was selected, and both the optimal coating and reference coating samples were analyzed. Based on the contact angle analysis results, the contact angle of the reference sample was measured to be 65.20 degrees, while the optimum coating sample was measured to be 87.4 degrees. According to the TG-DTA, the optimum coating exhibited a mass loss of 37.7. It was observed that both the reference and optimum coatings had a degradation temperature of similar to 408 degrees C. As a result of this study and analyzes, it was observed that the coating exhibited enhanced hydrophobic properties, increased mechanical strength, improved adhesion properties, and preserved its combustion characteristics.
Keywords: cocoa butter; coconut oil; organic coatings; titanium dioxide; CORROSION PROTECTION; PAINT; INSIGHTS; Chemistry; Food Science & Technology